Biostratigraphic, evolutionary, and paleoenvironmental significance of the southernmost lepidocyclinids of the Pacific coast of South America (East Pisco Basin, southern Peru). (December 2019) - Coletti, Giovanni; Bosio, Giulia; Collareta, Alberto; Malinverno, Elisa; Bracchi, Valentina Alice; Di Celma, Claudio; Basso, Daniela; Stainbank, Stephanie; Spezzaferri, Silvia; Cannings, Torin; Bianucci, Giovanni
Abstract: Lepidocyclinids are one of the most common group of Cenozoic large benthic foraminifera and, thanks to their clear evolutionary patterns, they are extensively used in biostratigraphy. They originated during the Eocene in the American region and then spread eastward, reaching a worldwide distribution in the Oligocene. This paper investigates the southernmost population of lepidocyclinids ever found along the Pacific coast of South America, located in the lower part of the Paracas Formation (Los Choros Member) of the East Pisco Basin of Peru. The examined Los Choros strata are composed of mixed siliciclastic-bioclastic coarse-grained deposits. The skeletal assemblage is dominated by large benthic foraminifera and mollusks with subordinate echinoids and barnacles, suggesting a deposition in a shallow, tropical, shelf environment with a moderate nutrient supply. The large benthic foraminiferal assemblage is largely dominated by Lepidocyclina rdouvillei . This species is extremely primitive, exhibiting ancestral characters such as a straight wall separating the protoconch and deuteroconch, very large principal auxiliary chambers and a poorly organized equatorial plane. The presence of common and primitive L. rdouvillei, supported by the associated occurrence of Polylepidina, suggests an age comprised between 43.6 Ma and 40.5 Ma for the Los Choros Member in the study area. This range is confirmed by nannofossil assemblages that indicate an age between 42.37 Ma and 40.34 Ma for the base of the overlying Yumaque Member of the Paracas Formation. These results highlight the potential of lepidocyclinids for biostratigraphy and paleoenvironmental reconstructions in South America. Highlights: Large benthic foraminifera of the Los Choros Member, Paracas Fm., East Pisco Basin. Southernmost lepidocyclinids population of the Pacific Coast of South American. The age of the Los Choros Member is constrained to the late Lutetian. The association indicates tropical climate during the deposition of the Los Choros Member.